PEMBERIAN PUPUK NITROGEN DAN PUPUK ORGANIK GRANUL TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (ALLIUM CEPA L.) - Manurung, Agnes Imelda; Sirait, Bilter A; Hulu, Tonasokhi; Marpaung, Robbert G (Universitas Medan Area, 2019)
This study aims to determine the response of growth and production of shallot (Allium cepa L.) to the Nitrogen fertilizer and Granule Organic fertilizer. The design used was a Factorial Completely Randomized Design consisting with two (2) treatment factors. The first factor is Nitrogen (N) from Urea which consists of three levels, namely: N1 = 2 g / plot, N2 = 4 g / plot and N3 = 6 g / plot. The second factor of Organic Granule fertilizer consisted of three levels, namely: G1 = 5 kg / plot, G2 = 10 kg / plot, G3 = 15 kg / plot. The results showed that interaction of Nitrogen fertilizer and Granul Organic fertilizer significantly affected plant height, number of leaves, number of tillers and tubers wet weight per plot, but not significant for the number of flower stalks. The highest growth and production of shallots produced a combination of treatment N3 = 6 g / plot and G3 = 15 kg / plot.